Mesoscale modeling of smoke transport from equatorial Southeast Asian Maritime Continent to the Philippines: First comparison of ensemble analysis with in situ observations. Issue 10 (19th May 2017) - Ge, Cui; Wang, Jun; Reid, Jeffrey S.; Posselt, Derek J.; Xian, Peng; Hyer, Edward
Abstract: Atmospheric transport of smoke from equatorial Southeast Asian Maritime Continent (Indonesia, Singapore, and Malaysia) to the Philippines was recently verified by the first‐ever measurement of aerosol composition in the region of the Sulu Sea from a research vessel named Vasco . However, numerical modeling of such transport can have large uncertainties due to the lack of observations for parameterization schemes and for describing fire emission and meteorology in this region. These uncertainties are analyzed here, for the first time, with an ensemble of 24 Weather Research and Forecasting model with Chemistry (WRF‐Chem) simulations. The ensemble reproduces the time series of observed surface nonsea‐salt PM2.5 concentrations observed from the Vasco vessel during 17–30 September 2011 and overall agrees with satellite (Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) and Moderate Resolution Imaging Spectroradiometer (MODIS)) and Aerosol Robotic Network (AERONET) data. The difference of meteorology between National Centers for Environmental Prediction (NCEP's) Final (FNL) and European Center for Medium range Weather Forecasting (ECMWF's) ERA renders the biggest spread in the ensemble (up to 20 μg m −3 or 200% in surface PM2.5 ), with FNL showing systematically superior results. The second biggest uncertainty is from fire emissions; the 2 day maximum Fire Locating and Modelling of Burning Emissions (FLAMBE) emission is superior than the instantaneous one. While Grell‐Devenyi (G3) and Betts‐Miller‐Janjić cumulus schemes only produce a difference of 3 μg m −3 of surface PM2.5 over the Sulu Sea, the ensemble mean agrees best with Climate Prediction Center (CPC) MORPHing (CMORPH)'s spatial distribution of precipitation. Simulation with FNL‐G3, 2 day maximum FLAMBE, and 800 m injection height outperforms other ensemble members. Finally, the global transport model (Navy Aerosol Analysis and Prediction System (NAAPS)) outperforms all WRF‐Chem simulations in describing smoke transport on 20 September 2011, suggesting the challenges to model tropical meteorology at mesoscale and finer scale. Plain Language Summary: It is well known that smoke particles from fires in Indonesia, Singapore, and Malaysia can affect each other's air quality. Less known and surely not well documented is the transport of smoke particles from these countries to the Philippines. Here we use the first‐ever measurements took nearby the coastal of the Philippines to analyze an ensemble of 24 WRF‐Chem simulations of smoke transport. Because of persistent cloud cover and the complexity of meteorology, mesoscale modeling of smoke transport in these regions normally has large uncertainties. We show these uncertainties are caused first by meteorology and then by fire emissions. We further show that models with finer resolution not necessarily produce better results. Key Points: First mesoscale modeling of smoke transport from equatorial Southeast Asian Maritime Continent to the Philippines Ensemble analysis of modeling uncertainties with first‐ever measurement of aerosol composition data in the region of the Sulu Sea Meteorological initial and boundary conditions, not cumulus parametrization and fire emission, have the largest uncertainty in the simulation